2017
DOI: 10.3390/rs9060525
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Monitoring the Spatial-Temporal Dynamics of Desertification in Response to Climate Change and Human Activities across the Ordos Plateau, China

Abstract: Abstract:The Ordos Plateau, a typical semi-arid area in northern China, has experienced severe wind erosion events that have stripped the agriculturally important finer fraction of the topsoil and caused dust events that often impact the air quality in northern China and the surrounding regions. Both climate change and human activities have been considered key factors in the desertification process. This study used multi-spectral Landsat Thematic Mapper (TM), Enhanced Thematic Mapper Plus (ETM+) and Operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 67 publications
(82 reference statements)
0
31
0
Order By: Relevance
“…Temperature and precipitation are used as inputs for the calculation of evapotranspiration. A thorough explanation of this model is discussed by Lieth [27,54,55] in detail.…”
Section: Pnpp and Hnpp Calculationmentioning
confidence: 99%
“…Temperature and precipitation are used as inputs for the calculation of evapotranspiration. A thorough explanation of this model is discussed by Lieth [27,54,55] in detail.…”
Section: Pnpp and Hnpp Calculationmentioning
confidence: 99%
“…At the beginning of the 21st century, a number of studies found that texture features, moisture content, and surface albedo changed with a change in ground object types [12]. At the same time, some researchers found that monitoring changes in vegetation and land use was not the only way to measure desertification [13,14]. Zeng et al used the albedo and NDVI (normalized difference vegetation index) to build the Albedo-NDVI feature space to conduct a study on desertification [15].…”
Section: Introductionmentioning
confidence: 99%
“…Surface albedo was used to extract soil brightness using Liang albedo [35]. Albedo is widely used as an indicator to assess desertification in arid and semi-arid areas [7,9,33,34,35,36,37,38,39]. Surface albedo was retrieved using S-2 imagery after pre-processing.…”
Section: Introductionmentioning
confidence: 99%